THE ROLE OF SERIAL RADIOGRAPHS TO DIAGNOSE DIABETIC FOOT BONE INFECTION. - ANTONIO LEONE; Nicola Carlo BIANCO; Giulia D'AMBRA; Salvatore LUCCHESI; Elisa LA ROSA; Amato INFANTE; Daniele PERLA; Consolato GULLI' (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Purpose: To evaluate the role of progressive radiographic changes to diagnose diabetic foot osteomyelitis.